Night and Darkness in Ancient Mesoamerica - Reed, David M.; Gonlin, Nancy (Book collections on Project MUSE., 2021)
"Incorporates how aspects of the natural world were imbued with deep cultural meanings and expressed by different peoples from different time periods in Mexico and Central America. Material culture, iconography, epigraphy, art history, ethnohistory, and ethnographies are used to illuminate dimensions of culture often neglected in reconstructions of the past"--